ANALYSIS OF SOME EXTERNAL VARIABLES OF THE AGRICULTURAL EXTENSION SYSTEM IN IRAQ ACCORDING TO THE SWOT MODEL - Challob, Mahmood; Salman, Mithal (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The research aimed to analyze some of the external environmental variables of the agricultural extension system in Iraq, namely (economic variables, and technological variables). To achieve the research objectives, a questionnaire was, consisting of (32) paragraphs The research community included all agricultural extension directors, numbering (220) respondents. The research results showed that there are several opportunities in the field of economic variables, where the paragraph (the abundance of resources and requirements available to provide extension services and activities) came in first place in terms of importance or the level of approval of the respondents on it with a weighted rate of (1.85) degrees, as for the field of technological variables, there are several opportunities, as the paragraph (the emergence of digital channels and programs specialized in extension and other agricultural aspects) obtained the first rank in terms of importance or the level of approval of the respondents. with a weighted rate of (2.77) degrees, Accordingly, we recommend that the responsible authorities in the Ministry of Agriculture and the Department of Agricultural Extension and Training adopt the results of the research, exploit the available opportunities, and confront the threats as much as possible, to reform the agricultural extension system.